2012
DOI: 10.3133/ofr20121154
|View full text |Cite
|
Sign up to set email alerts
|

Landscape consequences of natural gas extraction in Bradford and Washington Counties, Pennsylvania, 2004-2010

Abstract: Increased demands for cleaner burning energy, coupled with the relatively recent technological advances in accessing unconventional hydrocarbon-rich geologic formations, led to an intense effort to find and extract natural gas from various underground sources around the country. One of these sources, the Marcellus Shale, located in the Allegheny Plateau, is undergoing extensive drilling and production. The technology used to extract gas in the Marcellus Shale is known as hydraulic fracturing and has garnered m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…The Nature Conservancy has projected new well pad numbers and locations for Pennsylvania (Johnson, 2010), and is currently working on projections across the entire play (T. Gagnolet, personal communication), but predicting regional patterns of energy development is exceedingly complex. Furthermore, our analysis is limited to the impacts of gas development in the interior Marcellus shale, and does not include adjacent, less productive, areas of the Marcellus shale or other gas extraction development such as coalbed methane wells, which often occur in the same area (Slonecker et al, 2012), and which would increase the potential loss of habitat and the resulting reduction in species' ranges. Regardless of these limitations, our conservative estimates indicate that habitat loss will not be insignificant, as evidenced by our estimation of $20% forest loss throughout the ranges of these five species if the upper estimate of new well pads are developed.…”
Section: Discussionmentioning
confidence: 99%
“…The Nature Conservancy has projected new well pad numbers and locations for Pennsylvania (Johnson, 2010), and is currently working on projections across the entire play (T. Gagnolet, personal communication), but predicting regional patterns of energy development is exceedingly complex. Furthermore, our analysis is limited to the impacts of gas development in the interior Marcellus shale, and does not include adjacent, less productive, areas of the Marcellus shale or other gas extraction development such as coalbed methane wells, which often occur in the same area (Slonecker et al, 2012), and which would increase the potential loss of habitat and the resulting reduction in species' ranges. Regardless of these limitations, our conservative estimates indicate that habitat loss will not be insignificant, as evidenced by our estimation of $20% forest loss throughout the ranges of these five species if the upper estimate of new well pads are developed.…”
Section: Discussionmentioning
confidence: 99%
“…In Bradford County, there were over 1,000 active wells at the time of this study-more than in any other county in the state [25]. For each drilling site, an estimated nine acres per well pad, with an additional 21 acres of indirect edge effects, are converted for UNGDO operations, altering habitat and landscape through loss and fragmentation [26].…”
Section: Discussionmentioning
confidence: 99%
“…[157,158] Furthermore, depending on the site, roads may have to be constructed to allow equipment and materials to be transported. [116,159] All of this may also affect the local ecology,b ut the effects are still largely unknown, apart from afew studies.F or example,one study has suggested that specialized species and habitatsa round well pads are most at risk because of land and food-chain fragmentation.…”
Section: Land Usementioning
confidence: 99%